Investigation of the Recycling Practices on Construction Waste in Green Building Index (GBI) Projects - Affandi, Fahmi; Nagapan, Sasitharan (Recent Trends in Civil Engineering and Built Environment, 2022)
Construction sector is growing rapidly in constructing projects in urban and rural area. The sector using high volume of building materials. Due to the rate of construction waste increasing day by day, construction waste becoming a crucial issues in construction industry. The research conducted to investigate the recycling practices on construction waste in Green Building Index (GBI) Projects. The objective of this study is to determine the methods of the recycling practices on construction waste and to identify the benefits of the recycling practices on construction waste in GBI Projects. An online questionnaire survey through Google Form was used to collect data for this study. The questionnaire distributed to all construction professionals who are experienced in construction field. A total of 110 questionnaires were received from the construction professionals. The collected data was analysed by using mean score and ranking method. The three most suitable methods determined from the analysed are ‘Recycling should be carefully planned before starting and follows local regulations’ (mean score = 4.16), ‘Segregating metal waste on site’ (mean score = 4.15) and ‘Uses multiple container for each type of waste on site’ (mean score = 4.01). The top three of benefits are ‘Save large amounts of energy and decreases the consumption of natural resources to produce new materials’ (mean score = 4.17), ‘Enhance the companies public images’ (mean score = 4.13) and ‘Reduction of negative environmental effects’ (mean score = 4.12). The findings of this study useful for construction professionals in practicing recycling construction waste in GBI Projects.